Sosialisasi Pencegahan Covid-19 pada Anak-Anak di Dusun Talang Kabupaten Sukoharjo - Ikha Nadia Lilfitri; Dewi Candra Ciptosari; Widya Nur Aisa; Ratih Puspita Dewi (Sociology Department Of Syiah Kuala University, 2021)
This article is the result of community service activities. The purpose of this activity is to disseminate information about Covid-19 to children in Talang Hamlet. This socialization activity was carried out online with the Google Meet application with 19 children as participants from elementary to high school levels. The technique of delivering socialization uses the lecture method with PowerPoint media. This activity increased the knowledge of children in Talang Hamlet about the Covid-19 pandemic, especially about the dangers of Covid-19, prevention of Covid-19, and the application of health protocols during the Covid-19 pandemic. At the final stage of the activity, assistance was provided in necessities and hand sanitizer to local hamlet residents. This activity concluded that COVID-19 socialization activities for children could increase their knowledge about Covid-19.AbstrakArtikel ini merupakan hasil kegiatan pengabdian kepada masyarakat. Tujuan dari kegiatan ini adalah untuk menyebarluaskan informasi tentang Covid-19 kepada anak-anak di Dusun Talang. Kegiatan sosialisasi ini dilakukan secara online dengan aplikasi Google Meet dengan peserta 19 anak dari tingkat SD hingga SMA. Teknik penyampaian sosialisasi menggunakan metode ceramah dengan media PowerPoint. Kegiatan ini menambah pengetahuan anak-anak di Dusun Talang tentang pandemi Covid-19 khususnya tentang bahaya Covid-19, pencegahan Covid-19, dan penerapan protokol kesehatan selama pandemi Covid-19. Di akhir kegiatan, diberikan bantuan sembako dan hand sanitizer kepada warga dusun setempat. Kegiatan ini menyimpulkan bahwa kegiatan sosialisasi COVID-19 kepada anak-anak dapat menambah pengetahuan mereka tentang Covid-19.